The Cyber Attack on Saudi Aramco in 2012 - Alsaeed, Alaa (Asian Journal of Engineering and Applied Technology, 2021)
In recent years, information security has become a corporate priority due tothe large number of cyber-attacks that happen every day. These attacks could cause a regression in economic growth, which makes corporations another reason to defend their system. This paper provides an introduction to Saudi Aramco as well as an overview of its products. Then, the paper examines the Aramco cyber-attack in 2012. Aramco is a massive company with huge facilities that require powerful policies on security. Aramco should implement a Redundant Array of Independent Disks and Intrusion Detection System and review the log files on the server to protect its servers against attacks.